Hubungan Pengetahuan dan Motivasi Ibu dengan Kepatuhan Imunisasi Pada Balita di Lembang Tondon Wilayah Kerja Puskesmas Tondon Kabupaten Toraja Utara Tahun 2022 - Manguma, Chris; Manguma, Etty (Universitas Airlangga, 2025)
Background: Immunization plays a crucial role in reducing infant mortality and morbidity from vaccine-preventable diseases and should be administered from birth. Immunization is a crucial preventive measure to protect children from various preventable and dangerous diseases. However, preliminary interviews with five mothers in the Tondon Community Health Center area revealed persistent discrepancies in immunization implementation. Objectives: This study aims to examine the relationship between maternal knowledge and motivation and their compliance with immunization schedules for toddlers in Lembang Tondon, within the working area of the Tondon Health Center, North Toraja Regency, in 2022. Methods: A retrospective, cross-sectional design was employed, where data on both independent and dependent variables were collected simultaneously. The study population included all mothers of toddlers in Lembang Tondon, totaling 129, with a sample size of 97 mothers selected for participation. Data collection occurred from August to November 2022 using questionnaires and child health monitoring books. Data analysis was conducted using the Chi-Square test. Results: The findings revealed that most mothers had good knowledge about immunization (60 respondents or 61.9%), high motivation to immunize their children (71 respondents or 65.9%), and complied with immunization guidelines (63 respondents or 64.9%). The p-value for maternal knowledge was 0.002 (<0.05) and for motivation, it was 0.000 (<0.05), indicating statistical significance. Conclusion: The study concludes that there is a significant relationship between maternal knowledge and compliance with toddler immunization, as well as between maternal motivation and immunization compliance, in Lembang Tondon. Although all toddlers in the study had received immunizations, some had not been immunized according to the recommended schedule, indicating a gap in maternal adherence to timely immunization.